Peran Orang Tua dalam Membimbing Anak Belajar dari Rumah di Masa Pandemi Covid-19: Studi Kasus Orang Tua dengan Pekerjaan sebagai Pegawai Negeri Sipil - Fitriah, Fitriah; Asyriah, Noor; Amrullah, M. Kholis; Hidayatullah, Hidayatullah (Tapis: Jurnal Penelitian Ilmiah, 2021)
The role of parents in guiding their children to study from home or study online is very important, especially for children at the elementary school level, because during the learning process, sometimes children did not understand what to do for the assignments, and some of them cannot operate the learning supporting devices properly. This condition challenges parents, because they must guide their children to study from home and derive their responsibility as Civil Servants that must be completed and cannot be abandoned. This research was a case study that examined the role of parents who work as Civil Servants in guiding their children to study from home during the Covid-19. The data collection techniques used were semi-structured interviews, observation, and documentation to 8 parents and their children. The study found that there were three roles of civil servant parents in guiding their children to study from home. Those roles were as a teacher in which parents teach subjects that must be mastered by their children in accordance with the educational curriculum; a facilitator in which parents provide children's needs to support the online learning process, and a motivator in which parents maintain the learning motivation of their children by giving the reward or punishment and attention.